Estudo retrospectivo da casuística clínica e de óbitos em mico-leão-da-cara-dourada (Leontopithecus chrysomelas) no Zoológico de São Paulo, no período de 2016 a 2023 - Monzon, Kelly de Santis Comar (2023)
The golden-headed lion tamarin (Leontopithecus chrysomelas) (Kuhl, 1820) belonging to the family Callitrichidae is a New World primate that is classified as endangered in the wild. Leontopithecus chrysomelas is an endemic species of the Atlantic Forest occurring in forest remnants and cabruca areas of Bahia. Due to loss, fragmentation and disconnection of habitat, the species is in population decline, requiring studies and actions aimed at its preservation. The identification of diseases that affect New World primates is of great importance in public health and in situ and ex situ conservation programs, due to the risk of anthropogenic influences creating conditions for infectious diseases to decimate entire populations of wild animals. Therefore, the investigation of diseases in these animals is of great relevance for conservation medicine and for the purposes of One Health. A retrospective survey of the clinical case series and deaths involving individuals of Leontopithecus chrysomelas from the São Paulo Zoo was carried out from January 2016 to July 2023, through the analysis of medical records, findings from clinical/physical, hematological, histopathological examinations, ultrasonographic and necropsy findings, to evaluate the case series, clinical manifestations and diagnoses. The data was spreadsheeted and the changes analyzed. Thirty-eight individuals were treated by the Veterinary Medicine Sector at the São Paulo Zoo, in a total of 196 care carried out. Nineteen deaths occurred during the period under study. Although hepatic/hepatobiliary disease/hepatic failure was the most evident clinical case during the consultations, and several of the animals presented gallstones and/or hepatic neoplasia, in the final diagnoses (histopathological examination after necropsy) and cause of death the most common disorders affected the renal system.